Governance for development in Africa : solving collective action problems - Booth, David, 1945-; Cammack, Diana Rose, 1945- (London ; New York : Zed Books, 2013)
"Drawing on in-depth empirical research spanning a number of countries in Africa, Booth and Cammack's path-breaking book offers both an accessible overview of issues surrounding governance for development on the continent, whilst also offering a bold new alternative. In doing so, they controversially argue that externally imposed 'good governance' approaches make unrealistic assumptions about the choices leaders and officials are, in practice, able to make. As a result, reform initiatives and assistance programmes supported by donors regularly fail, while ignoring the potential for addressing the causes rather than the symptoms of this situation. In reality, the authors show, anti-developmental behaviours stem from unresolved - yet in principle soluble - collective action problems." -- Publisher website.
Introduction -- From 'good governance' to governance that works -- The country contexts -- Maternal health : why is Rwanda doing better than Malawi, Niger and Uganda? -- The politics of policy incoherence and provider indiscipline -- The space for local problem-solving and practical hybridity -- Conclusion -- Bibliography -- index.
Includes bibliographical references (pages 140-154) and index.
BIGD
Keywords: Africa -- Politics and government -- 21st century